An Infrared Spectroscopic Study on Hofmann Type Complexes of Dimethyl Sulphoxide - Bayarı, Sevgi; Kantarci, Ziya; AKYÜZ, SEVİM (Elsevier, 1995)
The infrared spectra of M(DMSO)2NI(CN)4 (M = Mn, Co, Fe, Cu; DMSO = dimethyl sulfoxide) and M(DMSO)(py)Ni(CN)4, (M = Mn, Ni; py = pyridine) complexes are reported. In all the complexes, the SO stretch is shifted to a lower frequency than in the free molecule, indicating coordination through oxygen. Several modes of the pyridine in the M(DMSO)(py) Ni(CN)4 complexes have upward shifts in frequency compared to those in the free molecule, indicating that the molecule does not act as a guest molecule in the M(DMSO)2Ni(CN)4 host lattice, but is bonded directly to the metal (M) together with dimethyl sulfoxide.